Second Year Analysis of a Hybrid Schedule High School - James B. Schreiber; William R. Veal; David J. Flinders; Sherry Churchill (Arizona State University, 2001)
The current study examined two independent sophomore cohorts from a mid-western high school that had implemented a multi-schedule system (i.e., traditional, block, hybrid). The purpose of the study was to examine differences among the schedule types, gender, and GPA group on a state mandated standardized test. Analysis of covariance was used to examine the differences. Results indicate that a significant difference among schedule types was observed for only one cohort and for only one test (mathematics-computation). Results also indicate that schedule type did not significantly interact with gender or GPA group. The authors conclude that for these cohorts the type of schedule does not negatively or positively influence achievement.